Feline Hyperesthesia Syndrome - Case Report (Revista de Ciências Agroveterinárias, 2020)
Feline Hyperesthesia Syndrome (FHS) is a clinical condition, characterized by involuntary muscle contractions and changes in behavior. It is a rare syndrome, often of unknown origin, and the most common associated causes are skin related disorders, such as bacterial, fungal dermatitis, allergics and immune-mediated diseases. Causes related to the central nervous system and behavioral disorders are also reported. The clinical signs are varied, the diagnosis is often complex and the treatment varies according to the underlying cause. The purpose of this case report is to describe a case of FHS of possible dermatological etiology. A three-year-old Siamese male feline was treated for feline lower urinary tract disease throughout the duration of nine days. Associated, the animal also presented erythematous areas and hypotrichosis all over the face, especially around the eyes, nose and auricular pavilions, along with painful hypersensitivity to the touch and skin fasciculations in the lumbar and coccygeal region and pelvic limbs. An histopathological exam of the skin lesions was performed, where a chronic, superficial perivascular dermatitis was seen to be proliferative. Based on physical examination findings and additional tests, the animal was diagnosed with feline hyperesthesia syndrome secondary to dermatopathy.
Keywords: behavioral disorder; neurology; pemphigus